Aplikasi Visualisasi 3D Pada Struktur Sistem Rangka Manusia Berbasis Android - Satya Arisena Hendrawan; R. Rizal Isnanto; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
The development of information technology has penetrated into various aspects of human life that it can perform an active role on information technology. In learning, for instance in the world of education, there are many simply interactive applications run on Android operating system . This application employs Unity 3D software as an editor. The initial step of making this final project is creating a design of user interface application. Waterfall Development used as methodology for developing this application. Stages of research method, requirements, design, implementation, testing, and maintenance. User application is capable to run all menus contained on the application of "3D Visualization of Human Skeleton Structure System". With this application android-based user can exercise anytime and anywhere, and this application can run well when tested using black-box and got positive results when tested to application user.